PENGARUH KEPUASAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. BPR BANK JOMBANG PERSERODA - Beni Samprastyo; Sulastri Irbayuni; Hesty Prima Rini (REVITALISASI : Jurnal Ilmu Manajemen, 2021)
Every company always has a desire to improve service quality through effective and efficient performance. Employees are human resources that need to be managed, studied and evaluated properly and correctly, with the hope of being able to produce creativity and innovation to achieve company goals. The purpose of this study was to determine the effect of Job Satisfaction (X1) and Work Discipline (X2) on Employee Performance.The populations in this study were all 46 employees of PT. BPR Bank Jombang Perseroda. The sampling method applied in this research is saturated sampling, which includes sampling the entire population, and the analytical methodology employed is Partial Least Square.The research findings and subsequent discussions led to the following conclusions: if a high sense of job satisfaction has an impact on enhancing employee performance, proper work discipline has an impact on enhancing employee performance.